Multi-Omics Analysis and Validation of Cell Senescence-Related Genes Associated with Non-Alcoholic Fatty Liver Disease - Gong J; Qin Z; Xiao Y; Li J; Wang Q; Lei L; Li J (Journal of Inflammation Research)
Jianhua Gong,1– 3,* Zhijie Qin,3,* Yihao Xiao,3,* Jixue Li,3 Qing Wang,3 Liping Lei,4 Jiangfa Li3 1Department of Hepatobiliary and Pancreatic Surgery, The First College of Clinical Medical Science, China Three Gorges University, Yichang, Hubei, 443003, People’s Republic of China; 2Department of Hepatobiliary and Pancreatic Surgery, Yichang Central People’s Hospital, Yichang, Hubei, 443003, People’s Republic of China; 3Department of Hepatobiliary and Pancreatic Surgery, The First Affiliated Hospital of Guilin Medical University, Guilin, Guangxi, 541001, People’s Republic of China; 4Department of geriatric medicine, The First Affiliated Hospital of Guilin Medical University, Guilin, Guangxi, 541001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianhua Gong, Department of Hepatobiliary and Pancreatic Surgery, The First College of Clinical Medical Science, China Three Gorges University, Yichang Central People’s Hospital, No. 183 Yiling Ave, Yichang, Hubei, 443003, People’s Republic of China, Tel +86-13886703242, Email 38891488@qq.com Jiangfa Li, Department of Hepatobiliary and Pancreatic Surgery, The First Affiliated Hospital of Guilin Medical University, Guilin, Guangxi, 541001, People’s Republic of China, Tel +86-18907839510, Email 247546160@qq.comObjective: To assess causal links between senescence-related genes and non-alcoholic fatty liver disease (NAFLD) using summary-data Mendelian randomization (SMR) and colocalization analyses.Methods: Our study examined the relationship between senescence and NAFLD by integrating DNA methylation, gene expression, and protein quantitative trait loci (mQTL, eQTL, and pQTL) data. Summary statistics for NAFLD were sourced from a previous study (discovery) and the FinnGen database (replication), with additional cohorts for nonalcoholic steatohepatitis and liver fibrosis. Genetic variants near senescence-related genes were used as instrumental variables to assess causal relationships. Colocalization analysis was performed to confirm shared causal variants and liver-specific eQTL data were used for validation. Furthermore, we validated findings using cell and mouse models of NAFLD. Cell models were treated with oleic acid, and NAFLD mice were induced using a high-fat diet.Results: We identified 40 mQTLs, 9 eQTLs, and 3 pQTLs significantly linked to NAFLD in the discovery cohort. Multi-omics data highlighted three genes—S100A6, ENDOG, and TP53I3—as potential causal contributors. Notably, S100A6 was confirmed at both the methylation sites (cg24155129 and cg01910639) and gene expression levels, with methylation at these CpG sites significant regulating its expression. Liver-specific validation revealed that ENDOG expression was negatively associated with NAFLD, consistent with findings in blood. Finally, differential expression of all three genes was confirmed in cell models, with S100A6 and ENDOG further validated in a mouse model.Conclusion: Our findings suggest that S100A6, ENDOG, and TP53I3 are associated with NAFLD, providing insights for further research into the disease’s underlying etiology.Keywords: cellular senescence, non-alcoholic fatty liver disease, causal inference, Mendelian randomization, colocalization